2014
DOI: 10.2196/jmir.3529
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Applicability of E-Therapies for Depression, Anxiety, and Other Mood Disorders Among Lesbians and Gay Men: Analysis of 24 Web- and Mobile Phone-Based Self-Help Interventions

Abstract: BackgroundLesbians and gay men have disproportionately high rates of depression and anxiety, and report lower satisfaction with treatments. In part, this may be because many health care options marginalize them by assuming heterosexuality, or misunderstand and fail to respond to the challenges specifically faced by these groups. E-therapies have particular potential to respond to the mental health needs of lesbians and gay men, but there is little research to determine whether they do so, or how they might be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 35 publications
3
35
0
1
Order By: Relevance
“…We concur with Rozbroj and colleagues that e-therapies need to address the specific needs of lesbian, gay, bisexual or sexual minority people, so that these unique sub-populations can benefit from the rise of e-therapies. 17 We hope this rise will become a positive step towards reducing the disparities in mental health between heterosexual and non-heterosexual populations. 17 In the future we hope to modify Rainbow SPARX, incorporating the changes suggested by our study participants, and subsequently conduct a randomised controlled trial of the program.…”
Section: Table 1 (Continued)mentioning
confidence: 99%
See 1 more Smart Citation
“…We concur with Rozbroj and colleagues that e-therapies need to address the specific needs of lesbian, gay, bisexual or sexual minority people, so that these unique sub-populations can benefit from the rise of e-therapies. 17 We hope this rise will become a positive step towards reducing the disparities in mental health between heterosexual and non-heterosexual populations. 17 In the future we hope to modify Rainbow SPARX, incorporating the changes suggested by our study participants, and subsequently conduct a randomised controlled trial of the program.…”
Section: Table 1 (Continued)mentioning
confidence: 99%
“…17 We hope this rise will become a positive step towards reducing the disparities in mental health between heterosexual and non-heterosexual populations. 17 In the future we hope to modify Rainbow SPARX, incorporating the changes suggested by our study participants, and subsequently conduct a randomised controlled trial of the program.…”
Section: Table 1 (Continued)mentioning
confidence: 99%
“…This is helpful, as would be VR video that guides the user through social interactions, helping to self-regulate breathing and heart rate. 3 …”
Section: Social Anxietymentioning
confidence: 99%
“…Since lesbians and gay men have disproportionately high rates of depression and anxiety, it is important to develop apps to accommodate better mental health stressors specific to lesbians and gay men. 3 Mobile apps may also be used to help reduce health disparities. In one study, for those older than 65 years of age, a strong association was shown between perceived stigma and reluctance to seek out treatment.…”
Section: Future Directionsmentioning
confidence: 99%
“…In addition to higher rates of mental health problems compared to heterosexual youth and young adults, SSAYA also face greater barriers to accessing help such as feeling that mental health care services marginalise them by assuming heterosexuality and do not adequately assist them to address challenges unique to being same-sex attracted such as stigma and 'coming out' [ 27 ]. These barriers are intensified for SSAYA living in rural or regional areas where they have less access to relevant information, resources, support and services than their city peers.…”
Section: Introductionmentioning
confidence: 99%